Analytical hierarchical process to identify favorable areas to the coffee crop agroecosystem at municipal scale - Barros, Marco Aurélio; Moreira, Maurício Alves; Rudorff, Bernardo Friedrich Theodor (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to delimitate favorable areas to the coffee agroecosystem, in four municipalities of Minas Gerais State, Brazil, using the analytical hierarchical process (AHP). An arithmetic pondering function was obtained, based on the favorability premises to coffee crop production, with regard to the following variables: soil, slope, slope aspect, altimetry, and areas that should be under permanent protection. This function allowed to combine the adequate conditions to coffee crop cultivation and gave emphasis to the most favorable areas. It was observed that all four municipalities were different in terms of their favorability to the coffee agroecosystem; however, when considering only the coffee cultivated areas, it was observed that the municipalities of Boa Esperança and Cristais were not significantly different.